2017
DOI: 10.18203/2320-6012.ijrms20172097
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillectomy and its effect on ASO titre

Abstract: Background: Acute tonsillitis is one of the most common manifestations of the upper respiratory tract infections. It is common in children and accounts for an incidence of about 32 per 1000 patients per year. The objective of this study was to determine the effect of tonsillectomy on ASO titre and to evaluate the sensitivity and specificity of throat swab culture.Methods: Present study performed a prospective study, a total number of 50 children were screened, out which 25 patients under the age of 15 years (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Viswanathan et al [7] found that there was a marked reduction in the ASO titer level from the third month onwards after tonsillectomy and ASO continued to remain negative at six months and one year in a statistically significant level, in 88% of patients. Bharti et al [8] observed that there was a reduction in ASO titers to levels <200 IU/ml at 1, 2 and 3 months after tonsillectomy with a statistically significant difference (p =0.0001 for all). Kumar and Kumari [9] found that the mean ASOT readings before and 6 months after tonsillectomy were 518.29 and 117.13 IU/ml, respectively with a statistically significant difference (P value < 0.004)…”
Section: Discussionmentioning
confidence: 96%
“…Viswanathan et al [7] found that there was a marked reduction in the ASO titer level from the third month onwards after tonsillectomy and ASO continued to remain negative at six months and one year in a statistically significant level, in 88% of patients. Bharti et al [8] observed that there was a reduction in ASO titers to levels <200 IU/ml at 1, 2 and 3 months after tonsillectomy with a statistically significant difference (p =0.0001 for all). Kumar and Kumari [9] found that the mean ASOT readings before and 6 months after tonsillectomy were 518.29 and 117.13 IU/ml, respectively with a statistically significant difference (P value < 0.004)…”
Section: Discussionmentioning
confidence: 96%